Analisis Potensi dan Kesadaran Masyarakat dalam Pelaksanaan Zakat Pertanian di Desa Nogosari - Ika Purwaningsih (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Agricultural zakat is zakat that is paid after obtaining agricultural products and is obligatory in the Al-Qur'an and Hadith if the nisab has been met. With a nisab determined by the Department of Religion of 750 kg of rice and 1,350 kg of grain. With a percentage of 5% of the results where the land needs additional costs to be irrigated and 10% of the results where the land is irrigated without experiencing difficulties. The existing potential can be used in giving zakat, but it must be balanced with public awareness of the implementation of agricultural zakat. This type of research is field research which is descriptive qualitative research. The data sources obtained are primary and secondary data sources. Data collection through observation, interviews, documentation, invalidation of informants and using information such as books, journals, BAZNAS and BPS. After the data is collected, it is then analyzed by means of data reduction, presentation and drawing conclusions. The location of this research is in Nogosari Village, Pacet District, Mojokerto Regency. Based on the research results, the researchers managed to find that 1. The potential is 67 tons of grain or RP. Rp. 536,000,000 which can be used for agricultural zakat in Nogosari Village. 2. The Nogosari Village community's awareness of the implementation of zakat is quite good, but their understanding of agricultural zakat is still low, so they share some of their harvest as gratitude for the results they have obtained.